2007
DOI: 10.1002/bit.21537
|View full text |Cite
|
Sign up to set email alerts
|

High‐density transient gene expression in suspension‐adapted 293 EBNA1 cells

Abstract: Large-scale transient gene expression (TGE) in mammalian cells is an attractive method to rapidly produce recombinant proteins for pre-clinical studies, with some processes reported to reach 100 L. However, the yield remains low, hardly over 20 mg protein/L, mainly because the current TGEs have been performed at low cell density (approximately 5 x 10(5) cells/mL). In this study, the strategy to improve TGE focuses on facilitating transfection at high cell density. A high-density perfusion culture of 293 EBNA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 33 publications
1
26
1
1
Order By: Relevance
“…Anti-apoptosis engineering is one of many possible strategies that affect the physiological state of cells with significant benefits to TGE yields (Stettler et al, 2007). Future strategies should also capitalize on recent findings that TGE experiments without a medium exchange can lead to higher levels of recombinant protein production and simplified workflow (Backliwal et al, 2007;Sun et al, 2007). As the demand for faster development and expression of therapeutic protein grows in the biotechnology industry, the need for TGE is certain to increase in importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-apoptosis engineering is one of many possible strategies that affect the physiological state of cells with significant benefits to TGE yields (Stettler et al, 2007). Future strategies should also capitalize on recent findings that TGE experiments without a medium exchange can lead to higher levels of recombinant protein production and simplified workflow (Backliwal et al, 2007;Sun et al, 2007). As the demand for faster development and expression of therapeutic protein grows in the biotechnology industry, the need for TGE is certain to increase in importance.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in expression vector technology (Van Craenenbroeck et al, 2000) coupled with cell lines expressing the Epstein Barr virus (EBV) nuclear antigen 1 (EBNA1) or SV40 large-T antigen for episomal replication of the transfected vectors have allowed for significant gains in recombinant protein production (Durocher et al, 2002;Sun et al, 2007). By transfecting HEK 293 cells at very high densities (>1 Â 10 7 cells/mL) in perfusion culture (Sun et al, 2007) or by manual concentration methods (Backliwal et al, 2007), researchers have been able to obtain some of the highest yields of recombinant protein from TGE experiments. Further improvements in control of the culture environment by optimizing bioreactor conditions (Galbraith et al, 2006;Muller et al, 2007) or by applying alternative bioreactor technologies such as WAVE TM bags (Geisse and Henke, 2005) have also shown promise in enhancing TGE yields.…”
Section: Introductionmentioning
confidence: 99%
“…HEK293 cells readily take up DNA using various gene transfer vehicles such as calcium phosphate (Jordan et al 1998;Meissner et al 1999;Girard et al 2001;Meissner et al 2001;Durocher et al 2002;Baldi et al 2005), XtremeGENE Ro1539 (Schlaeger et al 1998;Schlaeger et al 2003) and PEI (Schlaeger and Christensen 1999;Durocher et al 2002;Pham et al 2003;Schlaeger et al 2003;Baldi et al 2005). Transient gene expression with PEI in a high-cell density perfusion culture was reported recently (Sun et al 2008). The HEK293 cell line is easily grown in suspension culture and can be adapted to serum free medium (Schlaeger et al 2003;Geisse et al 2003;Geisse and Henke 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported optimal efficiency of transfection using DNA concentration in the range of 0.4-0.6 μg per 10 6 cells in PEI-mediated protocols (Sun et al 2008;Kuroda et al 2009). Besides, PEI is known to have a toxic effect (Godbey and Mikos 2001;Kunath et al 2003;Sun et al 2008) and the concentration of PEI: DNA complex (polyplex) may influence the efficiency of the transient transfection. In the study described here, the highest polyplex amount resulted in higher cell death and significantly lower LV production.…”
Section: Effect Of Dna Concentration On Fviii Lentiviral Vector Produmentioning
confidence: 99%